Economic Foundations of the Organization of a Marketing and Logistics System in the Activities of Farms and Households (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
One of the biggest problems in Uzbekistan's agriculture is to adjust production volumes to the needs of the consumer market and to improve the system of product sales at the lowest cost. Today, dehkan farms and farmers producing products for the free market are faced with varying degrees of uncertainty in determining the volume of production, as a result of which there is a sharp fluctuation of prices in consumer markets, as well as high seasonal fluctuations in prices for the same type of product. This leads to negative consequences for both producers and consumers. Considering that our republic is specialized in the agricultural sector, and a large part of the production and service sectors, as well as more than 20 percent of the annual gross domestic product, are accounted for by agriculture, the development of the economy largely depends on agriculture. The article emphasizes the possibility of achieving relatively high efficiency of households and farming farms by reducing production costs and reducing the costs of selling products by ensuring the coordination of resource supply and marketing research in agriculture. At the same time, the article provides scientific ideas on taking into account market conditions in the production of products, planning production based on internal and external requirements, through conducting marketing and logistics research for households and farmers producing agricultural products. It also analyzes scientific work on increasing the investment attractiveness of the sector, and researching consumer and resource markets.